Application of Rotation Rate Sensors in Modal and Vibration Analyses of Reinforced Concrete Beams - Piotr Adam Bońkowski; Piotr Bobra; Zbigniew Zembaty; Bronisław Jędraszak (Sensors, 2020)
The recent rapid development of rotation rate sensor technology opens new opportunities for their application in more and more fields. In this paper, the potential of rotational sensors for the modal analysis of full-scale civil engineering structural elements is experimentally examined. For this purpose, vibrations of two 6-m long beams made of ultra-high performance concrete (UHPC) were measured using microelectromechanical system (MEMS) rotation rate sensors. The beams were excited to vibrations using an impact hammer and a dynamic vibration exciter. The results of the experiment show that by using rotation rate sensors, one can directly obtain derivatives of mode shapes and deflection shapes. These derivatives of mode shapes, often called “rotational modes”, bring more information regarding possible local stiffness variations than the traditional transversal and deflection mode shapes, so their extraction during structural health monitoring is particularly useful. Previously, the rotational modes could only be obtained indirectly (e.g., by central difference approximation). Here, with the application of rotation rate sensors, one can obtain rotational modes and deflection shapes with a higher precision. Furthermore, the average strain rate and dynamic strain were acquired using the rotation rate sensors. The laboratory experiments demonstrated that rotation rate sensors were matured enough to be used in the monitoring and modal analyses of full-scale civil engineering elements (e.g., reinforced concrete beams).